Cobalt-free positive electrode material, preparation method thereof and lithium ion battery
By using the nanoscopic hydroxide oxide manganese to synthesize the front -drive body, and control the burning temperature, balance the formation of single -diagonal phase and diamond -shaped phase, solve the lack of cobalt -free positive electrode materials in terms of thermal stability and circulating performance, and achieve high high. Balance between discharge capacity and electrochemical stability.
Patent Information
- Application Number
- CN202411484403.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
AI Technical Summary
The existing cobalt-free cathode materials have shortcomings in thermal stability and cycling performance, and it is difficult to achieve a balance between high discharge capacity and chemical stability during the charge and discharge cycle.
By using the nanoscopic hydroxide oxide manganese as the raw material, the front -drive body synthesis, and the formation of polyhedron particles and irregular fine particles during thermal treatment, control the burning temperature between 700 and 900 ° C to balance the single oblique phase phase The formation of the diamond -shaped phase.
A cobalt-free positive electrode material provides additional charging capacity within the range of 4.4V-4.8V, and at the same time improves the stability and migration rate of lithium. The initial discharge capacity reaches 191.43mAh G-1. %.
Smart Images

Figure CN119370908A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a cobalt-free positive electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] With the development of electric vehicles, electronic devices, photovoltaic technology and wind power generation, the demand for energy storage systems with high energy density, high power, long cycle life, high safety and low cost has increased. At present, rechargeable lithium-ion batteries are widely used due to their excellent electrochemical properties. The performance of positive electrode materials plays a decisive role in the overall performance of lithium-ion batteries. Therefore, in order to obtain lithium-ion batteries with higher energy density, positive electrode materials with high specific capacity and high redox potential must be given priority.
[0003] LiCoO2 positive electrode material is widely used in portable lithium-ion batteries due to its high energy density, excellent cycle life and stability. However, the cost of cobalt raw materials is relatively high, so there are certain limitations to using it as a positive electrode material. LiNiO2 has a similar structure to LiCoO2 and has a lower redox potential. It is more likely to lose electrons and undergo oxidation reactions during charging, achieving higher lithium ion utilization. At the same time, it can release more specific capacity than LiCoO2 at the same cut-off voltage. However, this material has poor thermal stability and poses safety risks. LiMnO2 positive electrode material has a lower cost, but its charge and discharge stability is poor.
[0004] In recent years, people have proposed cation doping and synthesized cobalt-free lithium battery layer positive electrode material LiMn 0.5 Ni 0.5 O2, discharge capacity is 108-170 mAh g -1 However, although nickel-rich and lithium-rich layer materials are expected to replace cobalt-containing active materials as the positive electrode of lithium-ion batteries, their shortcomings such as poor thermal stability, unstable charging and discharging, spontaneous reaction and adverse phase change cannot be solved, affecting the electrochemical properties and storage performance of the materials. In order to improve the thermal stability and cycle performance of cobalt-free positive electrode materials, cobalt-free positive electrode materials can be modified. Commonly used modification methods include doping and coating, but it is difficult to evenly disperse the coating material on the surface of the material particles during the coating process, and it cannot maximize the improvement effect. Summary of the invention
[0005] Based on this, the purpose of the present invention is to provide a cobalt-free positive electrode material and a preparation method thereof and a lithium ion battery. The cobalt-free positive electrode material of the present invention can control the good mixing of structural phases and achieve a balance between high discharge capacity and chemical stability during the charge and discharge cycle.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a cobalt-free positive electrode material, which comprises the following steps:
[0008] S1. After dissolving the manganese salt in pure water, adding ammonia water and letting it stand, then quickly adding hydrogen peroxide and stirring to obtain a mixed slurry A, heating the mixed slurry A and cooling it to room temperature, washing, precipitating, centrifuging, and drying to obtain manganese hydroxide in the form of nanorods;
[0009] S2. dissolving the nanorod-shaped manganese hydroxide together with lithium salt and nickel salt in pure water, adding ammonia, propylene glycol and oxalic acid to obtain a mixed slurry B, and drying the mixed slurry B to obtain a precursor;
[0010] S3. After calcining the precursor, a cobalt-free positive electrode material is obtained.
[0011] The cobalt-free positive electrode material prepared by the present invention uses manganese hydroxide in the form of nanorods as a raw material for precursor synthesis, and promotes the formation of two types of particles, polyhedral particles and irregular fine particles, during the heat treatment process. The content of Mn in the polyhedral particles is relatively large, and the content of Ni in the irregular fine particles is relatively large, so that a monoclinic phase and a rhombohedral phase are formed. The monoclinic phase helps to provide additional charging capacity within the range of 4.4V-4.8V, while the rhombohedral phase improves the stability and mobility of lithium. The present invention controls the calcination temperature between 700 and 900°C, which helps to balance the monoclinic phase and the rhombohedral phase, and at the same time controls the material particle size to ensure a high lithium ion mobility. The initial discharge capacity of the cobalt-free positive electrode material prepared by the present invention can reach 191.43 mAh g -1 , at 20mAhg -1 After 100 cycles, the capacity retention rate can reach 87.6%, achieving a balance between high discharge capacity and electrochemical stability during the charge and discharge cycle; the cobalt-free positive electrode material prepared by the present invention has excellent crystal phase distribution and suitable particle size, achieving a balance between high discharge capacity and electrochemical stability during the charge and discharge cycle, and is a low-cost cobalt-free positive electrode material with excellent electrical properties.
[0012] As a further improvement of the above solution of the present invention, the method for preparing the cobalt-free positive electrode material further comprises the following steps:
[0013] S4. Immersing the cobalt-free cathode material in a polydopamine solution, stirring at room temperature, and then centrifuging, washing and drying to obtain a cobalt-free cathode material containing a polydopamine precoat layer;
[0014] S5. Dissolve hydrated zirconium oxide nitrate in ethanol, and stir at room temperature to obtain a zirconium oxide solution, add the cobalt-free positive electrode material containing the polydopamine pre-coating layer to the zirconium oxide solution to obtain a mixture, heat and stir the mixture until all the ethanol is evaporated, and then dry and anneal to obtain a cobalt-free positive electrode material coated with zirconium oxide.
[0015] As a further improvement of the above scheme of the present invention, in step S1, the manganese salt is manganese acetate tetrahydrate;
[0016] And / or, in step S1, the molar ratio of the manganese salt to the ammonia water is 1:1-4;
[0017] And / or, in step S1, the molar ratio of the manganese salt to the hydrogen peroxide is 1:2-4;
[0018] And / or, in step S1, the heating is heating the mixed slurry A at 120°C-140°C for 18-20h.
[0019] As a further improvement of the above solution of the present invention, step S2 is specifically as follows:
[0020] S21. The nanorod-shaped manganese hydroxide, lithium salt and nickel salt are dissolved in pure water, and ammonia is added to adjust the pH value of the solution to 6.0-6.2 to precipitate nickel oxide on the surface of the nanorods;
[0021] S22. Then, pure water, propylene glycol and oxalic acid are added to the solution, heated and stirred to obtain a mixed slurry B, and the mixed slurry B is dried to obtain a precursor.
[0022] As a further improvement of the above solution of the present invention, in step S2, the lithium salt is lithium acetate, and the nickel salt is nickel acetate;
[0023] And / or, in step S2, in the mixed slurry B, the molar ratio of manganese element, lithium element and nickel element is 0.2-0.8:1-1.1:0.2-0.8;
[0024] And / or, in step S22, the volume ratio of propylene glycol to the solution after adding pure water is 1:5-10, and the molar ratio of oxalic acid to the transition metal element in the solution is 1:2-4;
[0025] And / or, in step S22, the heating is heating to 100°C-140°C.
[0026] As a further improvement of the above solution of the present invention, in step S3, the calcination temperature is 700-950° C., and the calcination time is 10-15 hours.
[0027] As a further improvement of the above scheme of the present invention, in step S4, the polydopamine solution uses tris buffer solution and methanol as co-solvents, the volume ratio of tris buffer solution to methanol is 1:1, and the concentration of the tris buffer solution is 1-30 mmol / L;
[0028] And / or, the mass ratio of the polydopamine to the cobalt-free positive electrode material is 1:0.5-2.
[0029] As a further improvement of the above solution of the present invention, in step S5, in the mixture, the mass ratio of zirconium oxide to the cobalt-free positive electrode material containing the polydopamine pre-coating layer is 1%-5%;
[0030] And / or, in step S5, the annealing temperature is 350-450° C., and the annealing time is 2-3 hours.
[0031] The present invention also provides a cobalt-free positive electrode material, which is prepared by the method for preparing the cobalt-free positive electrode material as described above.
[0032] The present invention also provides a lithium ion battery, which comprises the cobalt-free positive electrode material as described above.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1. The cobalt-free positive electrode material prepared by the present invention uses manganese hydroxide in the form of nanorods as a raw material for precursor synthesis, and promotes the formation of two types of particles, polyhedral particles and irregular fine particles, during the heat treatment process. The content of Mn in the polyhedral particles is relatively large, and the content of Ni in the irregular fine particles is relatively large, so that a monoclinic phase and a rhombohedral phase are formed. The monoclinic phase helps to provide additional charging capacity in the range of 4.4V-4.8V, while the rhombohedral phase improves the stability and mobility of lithium. The present invention controls the calcination temperature between 700 and 900°C, which helps to balance the monoclinic phase and the rhombohedral phase, and at the same time controls the material particle size to ensure a higher lithium ion mobility. The initial discharge capacity of the cobalt-free positive electrode material prepared by the present invention can reach 191.43 mAh g -1 , at 20mAhg -1 After 100 cycles, the capacity retention rate can reach 87.6%, achieving a balance between high discharge capacity and electrochemical stability during the charge and discharge cycle, and is a low-cost cobalt-free positive electrode material with excellent electrical properties. The cobalt-free positive electrode material prepared by the present invention has excellent crystal phase distribution and suitable particle size, achieving a balance between high discharge capacity and electrochemical stability during the charge and discharge cycle, and is a low-cost cobalt-free positive electrode material with excellent electrical properties.
[0035] 2. The present invention further performs zirconium oxide coating on the prepared cobalt-free positive electrode material, and uses polydopamine as a pre-coating layer to assist the coating of zirconium oxide, thereby ensuring uniform coverage of zirconium oxide. The initial discharge capacity of the modified positive electrode material is 193.91 mAh g -1 After 100 cycles, the capacity retention rate is 89.8%, which further improves the cycle performance and thermal stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1This is a graph showing the first constant current charge and discharge curve of the cobalt-free positive electrode material prepared in Example 2 of the present invention under 0.2C conditions;
[0037] Figure 2 This is a graph showing the first constant current charge and discharge curve of the cobalt-free positive electrode material coated with zirconium oxide prepared in Example 4 of the present invention under 0.2C conditions. DETAILED DESCRIPTION
[0038] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.
[0039] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0040] Example 1
[0041] This embodiment provides a cobalt-free positive electrode material, and the preparation method thereof comprises the following steps:
[0042] Manganese acetate tetrahydrate was dissolved in pure water, and then ammonia water was added dropwise, with the molar ratio of manganese acetate tetrahydrate to ammonia water being 1:1.5. After standing for 30 minutes, hydrogen peroxide was quickly added, with the molar ratio of manganese acetate tetrahydrate to hydrogen peroxide being 1:2. The mixture was stirred vigorously to obtain a mixed slurry A. The mixed slurry A was placed in a high-temperature sterilizer and heated at 120° C. for 20 hours. After cooling to room temperature, the mixture was washed with distilled water and ethanol, and centrifuged at 6000 rpm for 6 times for 5 minutes to obtain manganese hydroxide in the form of nanorods.
[0043] Manganese oxyhydroxide, lithium acetate and nickel acetate were measured, and the molar ratio of manganese, lithium and nickel was controlled to be 0.5:1.05:0.5. Manganese oxyhydroxide, lithium acetate and nickel acetate were dissolved in pure water, and ammonia water was added to adjust the pH value of the solution to 6.04, so that nickel oxide was precipitated on the surface of the nanorods; pure water, propylene glycol (volume ratio with the solution was 1:10) and oxalic acid (molar ratio with the transition metal was 1:2) were added in sequence later, and stirred at 120°C, and the obtained mixed slurry B was dried under vacuum conditions in a high-temperature sterilizer at 140°C for 72 hours to evaporate the solvent and obtain a precursor, and the precursor mixture was calcined in an air atmosphere at 750°C for 12 hours to obtain a cobalt-free positive electrode material.
[0044] Example 2
[0045] This embodiment provides a cobalt-free positive electrode material, and the preparation method thereof comprises the following steps:
[0046] Manganese acetate tetrahydrate was dissolved in pure water, and then ammonia water was added dropwise, with the molar ratio of manganese acetate tetrahydrate to ammonia water being 1:2. After standing for 30 minutes, hydrogen peroxide was quickly added, with the molar ratio of manganese acetate tetrahydrate to hydrogen peroxide being 1:3. The mixture was stirred vigorously to obtain a mixed slurry A. The mixed slurry A was placed in a high-temperature sterilizer and heated at 140° C. for 18 hours. After cooling to room temperature, the mixture was washed with distilled water and ethanol, and centrifuged at 6000 rpm for 6 times for 5 minutes to obtain manganese hydroxide in the form of nanorods.
[0047] Manganese oxyhydroxide, lithium acetate and nickel acetate are measured, and the molar ratio of manganese, lithium and nickel is controlled to be 0.5:1.05:0.5. Manganese oxyhydroxide, lithium acetate and nickel acetate are dissolved in pure water, and ammonia water is added to adjust the pH value of the solution to 6.04, so that nickel oxide is precipitated on the surface of the nanorods; pure water, propylene glycol (with a volume ratio of 1:8 to the solution) and oxalic acid (with a molar ratio of 1:3 to the transition metal) are added in sequence, and stirred at 120°C. The obtained mixed slurry B is dried under vacuum conditions in a high-temperature sterilizer at 140°C for 72 hours to evaporate the solvent and obtain a precursor. The precursor mixture is calcined in an air atmosphere at 850°C for 12 hours to obtain a cobalt-free positive electrode material.
[0048] Example 3
[0049] This embodiment provides a cobalt-free positive electrode material, and the preparation method thereof comprises the following steps:
[0050] Manganese acetate tetrahydrate was dissolved in pure water, and then ammonia water was added dropwise, with the molar ratio of manganese acetate tetrahydrate to ammonia water being 1:3. After standing for 30 minutes, hydrogen peroxide was quickly added, with the molar ratio of manganese acetate tetrahydrate to hydrogen peroxide being 1:3. The mixture was stirred vigorously to obtain a mixed slurry A. The mixed slurry A was placed in a high-temperature sterilizer and heated at 120° C. for 20 hours. After cooling to room temperature, the mixture was washed with distilled water and ethanol, and centrifuged at 6000 rpm for 6 times for 5 minutes to obtain manganese hydroxide in the form of nanorods.
[0051] Manganese oxyhydroxide, lithium acetate and nickel acetate are measured, and the molar ratio of manganese, lithium and nickel is controlled to be 0.5:1.05:0.5. The manganese oxyhydroxide, lithium acetate and nickel acetate are dissolved in pure water, and ammonia water is added to adjust the pH value of the solution to 6.04, so that nickel oxide is precipitated on the surface of the nanorods; pure water, propylene glycol (with a volume ratio of 1:10 to the solution) and oxalic acid (with a molar ratio of 1:2 to the transition metal) are added in sequence, and stirred at 120°C. The obtained mixed slurry is dried under vacuum conditions in a high-temperature sterilizer at 140°C for 72 hours to evaporate the solvent and obtain a precursor. The precursor mixture is calcined in an air atmosphere at 950°C for 12 hours to obtain a cobalt-free positive electrode material.
[0052] Example 4
[0053] This embodiment provides a cobalt-free positive electrode material, and the preparation method thereof comprises the following steps:
[0054] The cobalt-free positive electrode material prepared in Example 2 was immersed in a polydopamine solution, wherein the mass ratio of polydopamine to the cobalt-free positive electrode material in the solution was 1:2, and the solution was stirred at room temperature for 30 minutes to obtain a mixed solution, wherein the polydopamine solution used a tris buffer solution with a concentration of 20 mmol / L and methanol as co-solvents, and the volume ratio of the tris buffer solution to methanol was 1:1; the mixed solution was then centrifuged, washed several times with ethanol and distilled water, and dried at 90°C for 24 hours to obtain a cobalt-free positive electrode material containing a polydopamine precoating layer; hydrated zirconium oxide nitrate was dissolved in ethanol, stirred at room temperature for 1 hour, and the cobalt-free positive electrode material containing a polydopamine precoating layer was placed in a zirconium oxide solution, wherein the mass ratio of zirconium oxide to the cobalt-free positive electrode material containing a polydopamine precoating layer was 2%, and the solution was stirred at 50°C until all the ethanol was volatilized, and then the sample was dried at 90°C for 24 hours, and annealed in air at 400°C for 3 hours to obtain a cobalt-free positive electrode material coated with zirconium oxide.
[0055] Test Case
[0056] The cobalt-free positive electrode materials prepared in Examples 1-4 were prepared as working electrodes: the cobalt-free positive electrode materials prepared in each example were mixed with superconducting carbon black and polyvinylidene fluoride dissolved in N-methylpyrrolidone at a mass ratio of 8:1:1, ground into slurry, evenly coated on aluminum foil, and dried in a vacuum oven at 90°C for 24 hours; the electrochemical performance test was carried out on the Arbin MSTAT4 battery test system using glass microfiber as a separator and lithium foil metal as a counter electrode. The test results are shown in Table 1.
[0057] Table 1
[0058] <![CDATA[Initial discharge specific capacity / mAh g -1 > Capacity retention after 100 cycles Example 1 189.88 68.95% Example 2 191.43 87.6% Example 3 167.25 54.61% Example 4 193.91 89.8%
[0059] From the results in Table 1, we can see that:
[0060] Compared with Examples 1-3, the first discharge specific capacities of the cobalt-free positive electrode material prepared by sintering at 750°C in Example 1 and the cobalt-free positive electrode material prepared by sintering at 950°C in Example 3 under 0.2C conditions are 189.88 mAhg -1 、167.25mAhg -1 The first discharge capacity of the cobalt-free cathode material sintered at 850°C in Example 2 under 0.2C conditions reached 191.43 mAhg -1 , indicating that the cobalt-free cathode material sintered at 850°C has the best performance; Figure 1 The initial constant current charge and discharge curve of the cobalt-free positive electrode material prepared in Example 2 is shown in FIG. Figure 1It can be seen that the cobalt-free cathode material prepared in the present invention has a higher initial discharge capacity, which is greatly improved compared with the existing binary cobalt-free cathode material; and the first discharge specific capacity of the cobalt-free cathode material coated with zirconium oxide prepared in Example 4 reaches 193.31 mAhg -1 , Figure 2 This is the initial constant current charge and discharge curve of the cobalt-free positive electrode material coated with zirconia prepared in Example 4. It can be seen that the electrical performance of the cobalt-free positive electrode material coated with zirconia prepared in Example 4 is improved compared with the cobalt-free positive electrode material before coating.
[0061] After 100 cycles, the capacity retention rates of the cobalt-free positive electrode material prepared by sintering at 750°C in Example 1 and the cobalt-free positive electrode material prepared by sintering at 950°C in Example 3 were 68.95% and 54.61%, respectively, while the capacity retention rate of the cobalt-free positive electrode material prepared by sintering at 850°C in Example 2 was still 87.6%, showing good cycle performance and stability; the capacity retention rate of the coated cobalt-free positive electrode material prepared in Example 4 after cycle was 89.8%, and the cycle performance and stability of the coated cobalt-free positive electrode material were improved compared with those before coating.
[0062] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0063] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a cobalt-free positive electrode material, characterized in that: It includes the following steps: S1. After dissolving the manganese salt in pure water, adding ammonia water and letting it stand, then quickly adding hydrogen peroxide and stirring to obtain a mixed slurry A, heating the mixed slurry A and cooling it to room temperature, washing, precipitating, centrifuging, and drying to obtain manganese hydroxide in the form of nanorods; S2. dissolving the nanorod-shaped manganese hydroxide together with lithium salt and nickel salt in pure water, adding ammonia, propylene glycol and oxalic acid to obtain a mixed slurry B, and drying the mixed slurry B to obtain a precursor; S3. After calcining the precursor, a cobalt-free positive electrode material is obtained.
2. The method for preparing a cobalt-free positive electrode material according to claim 1, characterized in that: The method for preparing the cobalt-free positive electrode material further comprises the following steps: S4. Immersing the cobalt-free cathode material in a polydopamine solution, stirring at room temperature, and then centrifuging, washing and drying to obtain a cobalt-free cathode material containing a polydopamine precoat layer; S5. Dissolve hydrated zirconium oxide nitrate in ethanol, and stir at room temperature to obtain a zirconium oxide solution, add the cobalt-free positive electrode material containing the polydopamine pre-coating layer to the zirconium oxide solution to obtain a mixture, heat and stir the mixture until all the ethanol is evaporated, and then dry and anneal to obtain a cobalt-free positive electrode material coated with zirconium oxide.
3. The method for preparing a cobalt-free positive electrode material according to claim 1, characterized in that: In step S1, the manganese salt is manganese acetate tetrahydrate; And / or, in step S1, the molar ratio of the manganese salt to the ammonia water is 1:1-4; And / or, in step S1, the molar ratio of the manganese salt to the hydrogen peroxide is 1:2-4; And / or, in step S1, the heating is heating the mixed slurry A at 120°C-140°C for 18-20h.
4. The method for preparing a cobalt-free positive electrode material according to claim 1, characterized in that: Step S2 is specifically as follows: S21. The nanorod-shaped manganese hydroxide, lithium salt and nickel salt are dissolved in pure water, and ammonia is added to adjust the pH value of the solution to 6.0-6.2 to precipitate nickel oxide on the surface of the nanorods; S22. Then, pure water, propylene glycol and oxalic acid are added to the solution, heated and stirred to obtain a mixed slurry B, and the mixed slurry B is dried to obtain a precursor.
5. The method for preparing a cobalt-free positive electrode material according to claim 4, characterized in that: In step S2, the lithium salt is lithium acetate, and the nickel salt is nickel acetate; And / or, in step S2, in the mixed slurry B, the molar ratio of manganese element, lithium element and nickel element is 0.2-0.8:1-1.1:0.2-0.8; And / or, in step S22, the volume ratio of propylene glycol to the solution after adding pure water is 1:5-10, and the molar ratio of oxalic acid to the transition metal element in the solution is 1:2-4; And / or, in step S22, the heating is heating to 100°C-140°C.
6. The method for preparing a cobalt-free positive electrode material according to claim 1, characterized in that: In step S3, the calcination temperature is 700-950° C. and the calcination time is 10-15 hours.
7. The method for preparing a cobalt-free positive electrode material according to claim 2, characterized in that: In step S4, the polydopamine solution uses tris buffer solution and methanol as co-solvents, the volume ratio of tris buffer solution to methanol is 1:1, and the concentration of the tris buffer solution is 1-30 mmol / L; And / or, the mass ratio of the polydopamine to the cobalt-free positive electrode material is 1:0.5-2.
8. The method for preparing a cobalt-free positive electrode material according to claim 2, characterized in that: In step S5, in the mixture, the mass ratio of zirconium oxide to the cobalt-free positive electrode material containing the polydopamine pre-coating layer is 1%-5%; And / or, in step S5, the annealing temperature is 350-450° C., and the annealing time is 2-3 hours.
9. A cobalt-free positive electrode material, characterized in that: The cathode material is prepared by the method for preparing a cobalt-free cathode material as claimed in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: It includes the cobalt-free positive electrode material as claimed in claim 9.